A dynamical gluon mass solution in a coupled system of the Schwinger-Dyson equations - Aguilar, Arlene Cristina [UNESP]; Natale, Adriano Antonio [UNESP] (Springer Nature, 2004)
We study numerically the Schwinger-Dyson equations for the coupled system of gluon and ghost propagators in the Landau gauge and in the case of pure gauge QCD. We show that a dynamical mass for the gluon propagator arises as a solution while the ghost propagator develops an enhanced behavior in the infrared regime of QCD. Simple analytical expressions are proposed for the propagators, and the mass dependency on the ΛQCD scale and its perturbative scaling are studied. We discuss the implications of our results for the infrared behavior of the coupling constant, which, according to fits for the propagators infrared behavior, seems to indicate that α s(q2) → 0 as q2 → 0. © SISSA/ISAS 2004.
Keywords: Nonperturbative Effects; QCD